How Iranian families response to the conditions affecting elderly primary health care. - Darani, Firoozeh Mostafavi; Mohd. Riji, Haliza; Abedi, Heidarali; Ahmad, Shamsuddin; Abd Latiff, Latiffah (Medwell Journals, 2010)
In response to the need for effective elderly primary health care programs in the Islamic Republic of Iran, the present study sought to determine the nature of family's caring behaviors related to the elderly primary health care in an urban area in Iran. A qualitative research was conducted through 24 in-depth interviews, 4 focus groups (8 participants in each group) and participants observation. The following 2 main categories emerged from the analysis to describe family's caring behaviors: internal responses and external responses. This qualitative study has gathered data that could be used by policy makers and health care providers and researchers concerned with elderly health and their quality of life. Based on these findings, it is recommended that providing primary health care for the elderly should be embedded in a comprehensive approach which aims to change the conditions affecting the elderly primary health care in urban areas.